The use of ICT in supporting secondary school learner with disabilities: 2 case studies - Patne, Arjumand Khalil Ahmed (2019)
This mixed research study explores how information and communication technologies (ICT) which refers to all types of technology such as ipads helps secondary learners with special education needs and/ or disabilities (SEND) known in the UAE as determined students to communicate information. Both Participants came from secondary classrooms one identified as Non verbal Autistic on the higher spectrum and another a very gifted and talented student both using ICT. Both qualitative and quantitative data was obtained to examine practices of technology integration to support students in the special education classroom. Results showed that teachers value the role of various educational technologies to support student communication and enhance learning experiences for SEND students but face certain challenges. Participants also highlighted various practical considerations that teachers and schools should consider. The significance of the study in the field of educating SEND students are discussed. More research into the matter is required to explore which specific educational technologies are most beneficial for SEND student needs.